Facility network design by using k-mean and elbow method: a case of Indian handloom industry - Naik M.K.P.; Bhardwaj P. (My University, 2025)
Purpose: This study aims to design a facility network for the weavers to do direct business in the Indian handloom industry by using tourists as potential customers. Design/methodology/approach: Data from 4,001 weavers of the handloom industry and 82 tourist locations of Varanasi city were collected. This data was analysed using the k-mean and elbow methods to determine the locations and the optimal number of collection centres, selling stores and warehouses to provide opportunities for the weavers to do direct business. Findings: The study's findings showed that a greater opportunity could be provided with four optimal collection centres and selling stores, along with two warehouses in the handloom industry of Varanasi city. These results provide valuable guidance for policymakers to plan the Varanasi handloom network of facilities efficiently and effectively to improve the conditions of weavers. Originality/value: Determining the optimal locations is crucial for designing a facility network. The proposed network will aid the government and policymakers in comprehending and pinpointing potential sites to establish new facilities in the handloom industry in Varanasi, a city with tourism potential. © 2024, Emerald Publishing Limited.